Still focused on the Atlantic: accounting for the limited Europeanization of Portuguese security policy. Issue 1 (2nd January 2016) - Robinson, Steven
ABSTRACT: This article examines the limited Europeanization of contemporary Portuguese security policy and highlights how the persistence of North Atlantic Treaty Organisation (NATO) and the emergence of the Lusophone world have shaped Portuguese participation in the European Union's (EU's) Common Foreign and Security Policy in recent years, particularly in Common Security and Defence Policy (CSDP) missions in Africa and in the European Defence Agency's co-operation activities. Europeanization's conceptual weaknesses, combined with the mutually reinforcing nature of transatlantic, EU and Lusophone security co-operation, have reinforced the ambiguous nature of what a "Europeanized" vision for European security might look like, especially given long-standing loyalties to NATO. This affords states considerable margin for manoeuvrability in defining their security priorities, so long as they are seen as being broadly consistent. This article reassesses the appropriateness of the Europeanization concept and shows how Portugal has approached this strategic balancing act, supporting the development of the EU's CSDP whilst remaining loyal to NATO and seeking to develop security relations in the Lusophone world, achieving legitimacy by stressing complementarity and multilateralization in security co-operation.